2022
DOI: 10.1051/0004-6361/202142811
|View full text |Cite
|
Sign up to set email alerts
|

Redshifted methanol absorption tracing infall motions of high-mass star formation regions

Abstract: Context. Gravitational collapse is one of the most important processes in high-mass star formation. Compared with the classic blue-skewed profiles, redshifted absorption against continuum emission is a more reliable method to detect inward motions within high-mass star formation regions. Aims. We aim to test if methanol transitions can be used to trace infall motions within high-mass star formation regions. Methods. Using the Effelsberg-100 m, IRAM-30 m, and APEX-12 m telescopes, we carried out observations of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 117 publications
0
1
0
Order By: Relevance
“…Only a few studies have confirmed the 6.7 GHz line in absorption thus far (e.g. Menten 1991b; Pandian et al 2008;Impellizzeri et al 2008;Ortiz-León et al 2021;Yang et al 2022). Absorption in this line can occur towards radio continuum emission and the cosmic microwave background (CMB).…”
Section: Absorption Detectionsmentioning
confidence: 95%
“…Only a few studies have confirmed the 6.7 GHz line in absorption thus far (e.g. Menten 1991b; Pandian et al 2008;Impellizzeri et al 2008;Ortiz-León et al 2021;Yang et al 2022). Absorption in this line can occur towards radio continuum emission and the cosmic microwave background (CMB).…”
Section: Absorption Detectionsmentioning
confidence: 95%